PENGARUH PEMBIAYAAN ULTRA MIKRO SYARIAH TERHADAP KESEJAHTERAAN NASABAH PADA PNM MEKAAR SYARIAH DI DESA TANJUNG LAUT - Mayang Sari; Itsnaini Chusnul Khotimah; Hidayani (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
This study was conducted to determine financing in improving customer welfare at PNM Mekaar Syariah in Tajung Laut Village. The purpose of this study is to understand the effectiveness of financing in helping customers improve their welfare at PNM Mekaar in Tanjung Laut Village. This study employs a quantitative approach, which is a field research type, as it gathers information through direct observation in the field and data management. The types of data used in this study are primary data and secondary data, while the data sources in this study were obtained from the results of observations, questionnaires and documentation directly to customers. Data analysis techniques were carried out using instrument tests, classical assumption tests and simple linear regression analysis tests.The results of this study indicate that customer income increased after taking financing from PNM Mekaar Syariah in Tanjung Laut Village, because PNM provides various services that help customers develop their businesses. The expenses of customers who take financing at PNM have also been met, including food and non-food expenses. Financing from PNM Mekaar Syariah in Tanjung Laut Village has not been fully able to improve the level of family education, because one of the customers has not met the educational needs of one of his children. The health level of the customer's family has been improved through this financing, as evidenced by a healthy lifestyle, routine check-ups, and the purchase of health products. PNM has also improved the welfare of financing customers in terms of housing conditions and facilities owned in the household, this is supported by the results of distributing questionnaires directly to customers.